Work Environment and Fatigue Factors on Public Transportation Driver Productivity: A Cross-Sectional Study in Padangsidimpuan City - Lastari, Asdi; Permayasa, Nayodi; Pan Harahap, Dewi Arjuna Putri; J. Hadi, Anto (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Public transportation plays a vital role in supporting community mobility in Padangsidimpuan City, one of the cities located in North Sumatera Province. As a city with a relatively high urbanization rate and growing population density, the need for efficient public transportation is becoming increasingly urgent. Public transportation supports daily transportation needs and facilitates the community's economic, educational, and social activities. To analyze the factors of work environment and fatigue on the productivity of public transportation drivers in the city of Padangsidimpuan. Methods: This study is an observational study with a cross-sectional study design. The population and sample consisted of 145 city transportation public transportation drivers. The sampling technique used is total sampling (exhaustive sampling), and data analysis is carried out using chi-square tests and logistic regression. Results: The study showed that vehicle condition (p=0.001), road condition (p=0.001), noise level (p=0.001), and fatigue (p=0.001) were related to the productivity of public transportation drivers. At the same time, the most related variable is Exp. (B)= 29,649 road conditions. Conclusion: This study concludes that work environment factors, such as noise, road conditions, and fatigue, have a significant effect on the productivity of public transportation drivers in Padangsidimpuan City. Improving road conditions, managing noise, and reducing fatigue can increase driver productivity.